2018
DOI: 10.1039/c8dt01588k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and organic solar cell performance of BODIPY and coumarin functionalized SWCNTs or graphene oxide nanomaterials

Abstract: The synthesis and characterization of new hybrid materials based on reduced graphene oxide (rGO) or single walled carbon nanotubes (SWCNTs) covalently functionalized by 4,4'-difluoro-8-(4-propynyloxy)-phenyl-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene (BODIPY) (2) or 7-(prop-2-yn-1-yloxy)-3-(3',4',5'-trimethoxyphenyl)-coumarin (4) as light harvesting groups have been described. The organic solar cell performances of these novel nanomaterials in P3HT:PCBM blends were investigated. These covalently bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Electrochemical grade tetrabutylammonium hexafluorophosphate (TBAPF 6 ) in extra pure DCM was used as the supporting electrolyte in CV at a concentration of 0.10 mol dm −3 . High purity N 2 was used for deoxygenation of the solution for 10 min prior to each run and maintained in a nitrogen blanket [50,51]. HOMO-LUMO levels and band gap values provide further information on the potential use of a new molecule for many applications, such as dye-sensitized and organic also calculated by performing single-point time-dependent DFT (TD-DFT) calculations using the B3LYP/6-31 G (d, p) levels (Table 4).…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
“…Electrochemical grade tetrabutylammonium hexafluorophosphate (TBAPF 6 ) in extra pure DCM was used as the supporting electrolyte in CV at a concentration of 0.10 mol dm −3 . High purity N 2 was used for deoxygenation of the solution for 10 min prior to each run and maintained in a nitrogen blanket [50,51]. HOMO-LUMO levels and band gap values provide further information on the potential use of a new molecule for many applications, such as dye-sensitized and organic also calculated by performing single-point time-dependent DFT (TD-DFT) calculations using the B3LYP/6-31 G (d, p) levels (Table 4).…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 99%
“…BODIPY derivatives, acronym of boron-dipyrromethene (4,4-difluoro-4-bora-3 a ,4 a -diaza- s -indacene), have lately attracted wide research interest due to their remarkable photophysical properties: absorption-emission bands in the near UV–vis region, high fluorescence quantum yields (Φ f ) with an average lifetime between 1 and 10 ns, important molar absorption coefficients, and distinctive photochemical stability [ [1] , [2] , [3] ]. Consequently, the BODIPY unit has recently found potential application in a wide variety of fields such as laser technology, solar cell industry [ [4] , [5] , [6] , [7] ], bioimaging acquisition [ [8] , [9] , [10] ], photodynamic therapy [ 11 , 12 ], viscosity measurements [ 13 , 14 ], chemosensors [ 15 ], and electroluminescent devices [ 16 ], among other applications. BODIPY derivatives constitute a new generation of outstanding functional materials with characteristics suitable to be used as organic semiconductor (OS) materials [ [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%
“…Boron-dipyrromethene (BODIPY) and its derivatives have gained considerable attention in recent years. [28][29][30] Their exceptional photophysical properties, strong UV-absorbance, sharp fluorescence emission peaks, good solubility in numerous solvents, relative insensitivity towards polarity and pH variation along with rational stability under physiological conditions, make from these fluorescent dyes apposite agents for heavy metal and pesticide recognition. [31][32][33][34] Although numerous examples of cavitand derivatives have been reported in literature, few studies on these two groups (cavitand + BODIPY) combined are reported, [35][36][37][38] and to the best of our knowledge, there have been no report thus far describing the utility of such ionophore-fluorophore conjugates for heavy metal and pesticide recognitions on the cavitand derivatives.…”
Section: Introductionmentioning
confidence: 99%